Distributed Strain and Temperature Discrimination Using Two Types of Fiber in OFDR - Zhenyang Ding; Di Yang; Yang Du; Kun Liu; Yonghan Zhou; Rao Zhang; Zhexi Xu; Junfeng Jiang; Tiegen Liu (IEEE Photonics Journal)
We present a simple and effective method to achieve a distributed strain and temperature discrimination using two types of fiber by a Rayleigh backscattering spectra (RBS) shifts in optical frequency domain reflectometry. We paired two types of single mode fiber (SMF) side by side as the sensing fibers. One is the reduced-cladding (RC) SMF, and the other is the standard SMF. Since the RC SMF and the standard SMF have different sensitivity responses to strain and temperature variation, we can measure strain and temperature variation simultaneously by monitoring RBS shifts. We demonstrate that the measure errors are 0.31 °C in temperature and 7.97 μϵ in strain with a measurement range of 50 m and a spatial resolution of 18 cm.